2016
DOI: 10.3389/fpsyg.2016.00025
|View full text |Cite
|
Sign up to set email alerts
|

Can Gender-Fair Language Reduce Gender Stereotyping and Discrimination?

Abstract: Gender-fair language (GFL) aims at reducing gender stereotyping and discrimination. Two principle strategies have been employed to make languages gender-fair and to treat women and men symmetrically: neutralization and feminization. Neutralization is achieved, for example, by replacing male-masculine forms (policeman) with gender-unmarked forms (police officer), whereas feminization relies on the use of feminine forms to make female referents visible (i.e., the applicant… he or she instead of the applicant… he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
190
1
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(209 citation statements)
references
References 92 publications
(114 reference statements)
2
190
1
16
Order By: Relevance
“…In cases where the gender is unknown or indeterminate, or in languages where the traditional norm is to use a male pronoun to refer to all genders, a neutral pronoun should be used instead. 22 ‘They” is now widely accepted to have both singular and plural usages. The use of ‘(s)he’ or ‘him/her’ is better than exclusively defaulting to a male generic, although this terminology reinforces gender binaries and may still be problematic for transgender individuals.…”
Section: What Can You Do: Strategies To Avoid Gender Bias In Languagementioning
confidence: 99%
“…In cases where the gender is unknown or indeterminate, or in languages where the traditional norm is to use a male pronoun to refer to all genders, a neutral pronoun should be used instead. 22 ‘They” is now widely accepted to have both singular and plural usages. The use of ‘(s)he’ or ‘him/her’ is better than exclusively defaulting to a male generic, although this terminology reinforces gender binaries and may still be problematic for transgender individuals.…”
Section: What Can You Do: Strategies To Avoid Gender Bias In Languagementioning
confidence: 99%
“…Staying within the linguistic dimension, the tradition of research on the relationship between language and gender (see Freed, 2003) has come to deal with the use of sexist language in terms of its psychological and social impli- Research has shown the consequences of using this sexist form, finding that it undermines motivation, self-esteem, professional performance, and the effectiveness of women by threatening their sense of belonging (see e.g., Briere & Lanktree, 1983;Cameron, 1998;Cralley & Ruscher, 2005;Gaucher, Friesen, & Kay, 2011;McConnell & Fazio, 1996;Merkel, Maass, & Frommelt, 2012;Mucchi-Faina, 2005;Sczesny, Formanowicz, & Moser, 2016). This type of literature, in empirically showing the negative consequences of the usage of these specific linguistic forms on women themselves (see e.g., Bem & Bem, 1973;Crawford & English, 1984;Crawford & Unger, 2004;Gastil, 1990), also shows that these forms create a pervasive collective androcentric imaginary that renders women invisible (e.g., Ng, 2007;Stahlberg et al, 2007).…”
Section: Linguistic Sexismmentioning
confidence: 99%
“…It was found in the ninetieth of the 20th century. Modern researches illustrate the relevance and urgency of the topic of linguistically equal gender use (Horvath, L.K., Merkel, E.F., Maass, A. and Sczesny, S.,2016) including possible ways of avoiding linguistic female stereotyping and discrimination (Sczesny S, Formanowicz M., Moser, F., 2016), etc.…”
Section: Flourishing Creativity and Literacymentioning
confidence: 99%